Senescent Phenotype Induced by p90RSK-NRF2 Signaling Sensitizes Monocytes and Macrophages to Oxidative Stress in HIV-Positive Individuals: Implications for Atherogenesis. Issue 9 (26th February 2019) - Singh, Meera V.; Kotla, Sivareddy; Le, Nhat-Tu; Ae Ko, Kyung; Heo, Kyung-Sun; Wang, Yin; Fujii, Yuka; Thi Vu, Hang; McBeath, Elena; Thomas, Tamlyn N.; Jin Gi, Young; Tao, Yunting; et al.
Abstract : Background: The incidence of cardiovascular disease is higher in HIV-positive (HIV + ) patients than it is in the average population, and combination antiretroviral therapy (cART) is a recognized risk factor for cardiovascular disease. However, the molecular mechanisms that link cART and cardiovascular disease are currently unknown. Our study explores the role of the activation of p90RSK, a reactive oxygen species-sensitive kinase, in engendering senescent phenotype in macrophages and accelerating atherogenesis in patients undergoing cART. Methods: Peripheral whole blood from cART-treated HIV + individuals and nontreated HIV-negative individuals was treated with H2 O2 (200 µmol/L) for 4 minutes, and p90RSK activity in CD14 + monocytes was measured. Plaque formation in the carotids was also analyzed in these individuals. Macrophage senescence was determined by evaluating their efferocytotic ability, antioxidation-related molecule expression, telomere length, and inflammatory gene expression. The involvement of p90RSK-NRF2 signaling in cART-induced senescence was assessed by p90RSK-specific inhibitor (FMK-MEA) or dominant-negative p90RSK (DN-p90RSK) and NRF2 activator (NRF2A). Further, the severity of atherosclerosis was determined in myeloid cell-specific wild-type and DN-p90RSK transgenic mice. Results: Monocytes from HIV + patients exhibited higher levels of p90RSK activity and were also more sensitive to reactive oxygen species than monocytes from HIV-negative individuals. A multiple linear regression analysis involving cART, Reynolds cardiovascular risk score, and basal p90RSK activity revealed that cART and basal p90RSK activity were the 2 significant determinants of plaque formation. Many of the antiretroviral drugs individually activated p90RSK, which simultaneously triggered all components of the macrophage senescent phenotype. cART inhibited antioxidant response element reporter activity via ERK5 S496 phosphorylation. NRF2A reversed the H2 O2 -induced overactivation of p90RSK in cART-treated macrophages by countering the induction of senescent phenotype. Last, the data obtained from our gain- or loss-of-function mice conclusively showed the crucial role of p90RSK in inducing senescent phenotype in macrophages and atherogenesis. Conclusions: cART increased monocyte/macrophage sensitivity to reactive oxygen species- in HIV + individuals by suppressing NRF2-ARE activity via p90RSK-mediated ERK5 S496 phosphorylation, which coordinately elicited senescent phenotypes and proinflammatory responses. As such, our report underscores the importance of p90RSK regulation in monocytes/macrophages as a viable biomarker and therapeutic target for preventing cardiovascular disease, especially in HIV + patients treated with cART. Abstract : Supplemental Digital Content is available in the text.